Typification of Verbascum undulatum (Scrophulariaceae) - Zografidis, Aris (Phytotaxa, 2019)
Since the 1930’s, Verbascum undulatum Lamarck (1797: 221) has been the unambiguously applied name for a European-endemic species of mullein which was discovered by Tournefort in Greece in the early 18th century. However, as evidently indicated in the protologue, the binomial apparently represented the author’s perception of an unrelated taxon native to the Levant. To promote nomenclatural stability, the application of the name V. undulatum in its traditional sense is fixed with Tournefort’s illustration of the species serving as the lectotype. An epitype is also designated to facilitate future research in this variable species. The new synonymy of V. plicatum Sm. in Sibthorp & Smith (1806: 150) under the former name is proposed here and a lectotype is designated. The specimens have been consulted as digital images from the sources indicated except for the epitype and its duplicates which have been seen as physical specimens.